Olaparib tablets as maintenance therapy in patients with platinum-sensitive relapsed ovarian cancer and a BRCA1/2 mutation (SOLO2/ENGOT-Ov21): a final analysis of a double-blind, randomised, placebo-controlled, phase 3 trial. Issue 5 (May 2021) - Poveda, Andrés; Floquet, Anne; Ledermann, Jonathan A; Asher, Rebecca; Penson, Richard T; Oza, Amit M; Korach, Jacob; Huzarski, Tomasz; Pignata, Sandro; Friedlander, Michael; Baldoni, Alessandra; Park-Simon, Tjoung-Won; et al.
Summary: Background: Olaparib, a poly (ADP-ribose) polymerase (PARP) inhibitor, has previously been shown to extend progression-free survival versus placebo when given to patients with relapsed high-grade serous or endometrioid ovarian cancer who were platinum sensitive and who had a BRCA1 or BRCA2 ( BRCA1/2 ) mutation, as part of the SOLO2/ENGOT-Ov21 trial. The aim of this final analysis is to investigate the effect of olaparib on overall survival. Methods: This double-blind, randomised, placebo-controlled, phase 3 trial was done across 123 medical centres in 16 countries. Eligible patients were aged 18 years or older, had an Eastern Cooperative Oncology Group performance status at baseline of 0–1, had histologically confirmed, relapsed, high-grade serous or high-grade endometrioid ovarian cancer, including primary peritoneal or fallopian tube cancer, and had received two or more previous platinum regimens. Patients were randomly assigned (2:1) to receive olaparib tablets (300 mg in two 150 mg tablets twice daily) or matching placebo tablets using an interactive web or voice-response system. Stratification was by response to previous chemotherapy and length of platinum-free interval. Treatment assignment was masked to patients, treatment providers, and data assessors. The primary endpoint of progression-free survival has been reported previously. Overall survival was a key secondary endpoint and was analysed in all patients as randomly allocated. Safety was assessed in all patients who received at least one treatment dose. This trial is registered with ClinicalTrials.gov, NCT01874353, and is no longer recruiting patients. Findings: Between Sept 3, 2013 and Nov 21, 2014, 295 patients were enrolled. Patients were randomly assigned to receive either olaparib (n=196 [66%]) or placebo (n=99 [34%]). One patient, randomised in error, did not receive olaparib. Median follow-up was 65·7 months (IQR 63·6–69·3) with olaparib and 64·5 months (63·4–68·7) with placebo. Median overall survival was 51·7 months (95% CI 41·5–59·1) with olaparib and 38·8 months (31·4–48·6) with placebo (hazard ratio 0·74 [95% CI 0·54–1·00]; p=0·054), unadjusted for the 38% of patients in the placebo group who received subsequent PARP inhibitor therapy. The most common grade 3 or worse treatment-emergent adverse event was anaemia (which occurred in 41 [21%] of 195 patients in the olaparib group and two [2%] of 99 patients in the placebo group). Serious treatment-emergent adverse events were reported in 50 (26%) of 195 patients receiving olaparib and eight (8%) of 99 patients receiving placebo. Treatment-emergent adverse events with a fatal outcome occurred in eight (4%) of the 195 patients receiving olaparib, six of which were judged to be treatment-related (attributed to myelodysplastic syndrome [n=3] and acute myeloid leukaemia [n=3]). Interpretation: Olaparib provided a median overall survival benefit of 12·9 months compared with placebo in patients with platinum-sensitive, relapsed ovarian cancer and a BRCA1/2 mutation. Although statistical significance was not reached, these findings are arguably clinically meaningful and support the use of maintenance olaparib in these patients. Funding: AstraZeneca and Merck.